Vegetal species in the vernacular architecture of the highlands of Jujuy. Local criteria and public policies regarding conservation, sustainability and use (Huellas, 2023)
The use of natural resources in the highland region of Jujuy province, Argentina, is highly represented in various activities and practices. In this context, plant species have great relevance and roles in vernacular architectures and evidence a whole cultural conception, ways of connecting with the environment and exploitation logics. This paper aims at reflecting upon public policies related to the conservation of plant species in the Quebrada and Jujuy Puna. To achieve this, the role of plants in local constructive culture was characterized and state policies that have regulated these resources over time were reviewed. The ethnobotany classic methodology was used, with an intensive field work and ethnographic approach. Results show that the articulation of local and state criteria are the two necessary elements to guarantee the conservation of natural resources and the continuity of practices associated with them. It is necessary to reformulate the current regulations, which are restrictive and marginalizing of local traditions, and issue new regulations that control sustainable use respecting and promoting the traditional practices that characterize the region, in particular those related to the constructive culture.
Keywords: ethnobotany; conservation; sustainability; vernacular architecture